The Effect of Job Promotion and Mutation on Performance of Universitas Hasanuddin Civil Servant through Job Satisfaction. - Nurmawati Nurmawati; Cepi Pahlevi; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to analyze the effect of position and mutation on the performance of Hasanuddin University civil servants mediated by job satisfaction. This study uses a non probability sampling technique, so that all populations are sampled as many as 81 civil servant respondents within the Faculty of Engineering, Hasanuddin University. The research data was obtained from a questionnaire (primary), literature study and direct interviews with relevant parties according to the purpose of the study. The analysis technique uses multiple regression analysis consisting of structural models, measurement models and the sobel method. The results showed that, promotion had a positive and significant effect on job satisfaction showed, mutation had a positive and significant effect on job satisfaction indicating, job satisfaction had a positive and significant effect on performance, promotion had no positive and significant effect on performance, promotion had an effect on performance if mediated by job satisfaction variables, mutations have a positive and significant effect on performance mediated by job satisfaction.